Nurses in war voices from Iraq and Afghanistan - Scannell-Desch, Elizabeth; Doherty, Mary Ellen
This unique volume presents the experience of 37 U.S. military nurses sent to the Iraq and Afghanistan theaters of war to care for the injured and dying. The personal and professional challenges they faced, the difficulties they endured, the dangers they overcame, and the consequences they grappled with are vividly described from deployment to discharge. In mobile surgical field hospitals and fast-forward teams.